Feminization of Maroon Clownfish (Amphiprion biaculeatus, Bloch 1790) with 17β-Estradiol Hormonal Induction - Helena Sahusilawane; Agus Oman Sudrajat; Muhmmad Agus Suprayudi; Dinar Tri Soelistyowati; Ligaya I. T. A. Tumbelaka; Irzal Effendi (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research